Caracterização do sistema agropecuário dentro da agricultura familiar como subsídio de políticas públicas - Dantas, Lívia Aragão Correia (2013)
The objective of this study was to characterize the socioeconomic profile of the family farmers who live and work in Brazilian rural space and highlight the importance of family agribusiness through the significant relation between some variables as the value of the total production, GDP share in total area of the establishments, agricultural production and farmer income, that show the important participation of these farmers in agricultural productivity and consequently on the economy of country. Therefore, this sector deserves a greater attention and more investment in the development of public policies that lead to a quality education in rural areas, availability of technical courses for farmers, technical assistance more efficient and effective, as well as funding more readily available